"Discrimination" versus "Unfair Treatment": Measuring Differential Treatment and its Association with Health. Issue 4 (29th March 2019) - Grollman, Eric Anthony; Hagiwara, Nao
Abstract : There is consistent evidence of the health‐harming effects of discrimination. However, it remains unclear whether discrimination contributes to persistent racial and ethnic health disparities. One hindrance to documenting the association between discrimination and health disparities is ongoing methodological issues, particularly the role of question wording in assessing self‐reports of discrimination. Using two nationally representative surveys, we investigate whether the prevalence, distribution, and mental and physical health consequences of differential treatment vary by question wording—"discrimination" versus "unfair treatment." We find that "unfair treatment" yields greater reports of everyday forms of differential treatment relative to reports of "discrimination, " while the latter yields greater reports of major forms of differential treatment. In addition, the negative effect of "unfair treatment" on mental health is stronger than that of "discrimination, " while the latter has a stronger negative effect on physical health. However, the effect of question wording on reports of differential treatment and its association with health is largely unique to non‐Hispanic whites. We conclude that unfair treatment and discrimination reflect distinct concepts that should not be used interchangeably.